(untitled) (Fiep Bulletin - online, 2014)
OBJECTIVE: to examine the differences between the anthropometrics, adiposity and physical fitness indexes between boys and girls in the same chronological age. METHODS: the sample was composed by 28 boys and 42 girls in the age of 11 years and enrolled in a public school of Araucaria-PR. Fat percentage was calculated by the equation of BOILEAU et al. (1985), sit-and-reach test and hand grip test were performed according to JOHNSON and NELSON (1986) and SAFRIT (1986) and VO2 max was estimated using 20-m Shuttle Run test developed by LÉGER et al. (1986). Resting blood pressure (BP) was collected by the procedures suggested by ACSM (2003). Descriptive statistic and independent t test of Student were used to examine the differences of the variables studied between sexes, (p<0.05). RESULTS: there were significant differences found (p<0.05) for the fat percentage (19.0±7.4 and 23.5±7.0 %, respectively, boys and girls) and for the VO2 max (47.4±3.8 and 45.1±3.0 ml?Kg-1?min-1) between the studied sexes. There were not significant differences found between sexes for the variables body mass (36.6±8.1 and 38.1±9.7 Kg, boys and girls), body height (142.0±6.7 and 144.2±7.4 cm), resting systolic BP (89.4±12.8 and 94.6±15.7 mmHg) and diastolic BP (56.0±11.8 and 54.3±10.6 mmHg), BMI (18.0±3.2 and 18.1±3.5 Kg/m2), lean body mass (29.2±4.3 and 28.7±5.6 Kg), sit-and-reach test (27.0±5.5 and 27.2±6.4 cm), grip dynamometry of right hand (21.3±3.1 and 21.6±4.5 Kgf) and left hand (20.2±3.1 and 20.5±4.0 Kgf). CONCLUSION: They were not homogeneous between boys and girls as indicator of adiposity (fat percentage) and of cardiorespiratory fitness (VO2 max). The variable body mass, body height, resting blood pressure, BMI, flexibility and grip strength of right and left hands were similar between boys and girls.